Giving is a question of time: Response times and contributions to a real world public good - Johannes Lohse; Timo Goeschl; Johannes Diederich (University of Heidelberg, Department of Economics, 2014)
Recent experimental research has examined whether contributions to public goods can be traced back to intuitive or deliberative decision-making, using response times in public good games in order to identify the specific decision process at work. In light of conflicting results, this paper reports on an analysis of response time data from an online experiment in which over 3400 subjects from the general population decided whether to contribute to a real world public good. The between-subjects evidence confirms a strong positive link between contributing and deliberation and between free-riding and intuition. The average response time of contributors is 40 percent higher than that of free-riders. A within-subject analysis reveals that for a given individual, contributing significantly increases and free-riding significantly decreases the amount of deliberation required.
urn:nbn:de:bsz:16-heidok-170461
Keywords: 330; Public Goods; Cooperation; Dual Process Theories; Response Times; Climate Change; Online Experiment